PENGARUH DIGITAL MARKETING TERHADAP PENINGKATAN PENDAPATAN PELAKU USAHA MIKRO DI DESA ADAT BUALU - Ni Luh Wulani Parwati; Fahmi Tanjung; Yoviniani Yevri Yanseni; I Made Sujana (Yayasan Nusantara Hasana Berdikari, 2024)
Digital marketing has become an effective marketing strategy for increasing the competitiveness and revenue of micro-enterprises in the digital economy era. This study aims to analyze the influence of digital marketing on increasing the revenue of micro-enterprises in Bualu Traditional Village, Badung Regency, Bali. The use of social media and digital platforms can expand market reach and enhance interactions between businesses and consumers. Digital marketing significantly influences the increase in MSME revenue through improved promotion, market access, and marketing cost efficiency. The results show that the use of social media, marketplaces, and digital communication applications contributes positively to increasing sales volume and revenue of micro-enterprises in Bualu Traditional Village.